Inner Space of Freedom and the Issue of Man according to Józef Tischner - Dymarski, Zbyszek (Paedagogia Christiana, 2018)
This article is an attempt to look at the views of Józef Tischner on the issue of freedom. According to the author, Tischner’s way of thinking about that problem was most influenced by the views of three great European philosophers, Thomas Aquinas, Jean-Paul Sartre, and George Wilhelm Hegel. The author briefly discusses those theses that most inspired Tischner and those with which he polemicized. Tischner’s views on the issue of freedom were not just a compilation of the views of those thinkers. The philosopher went his own way. He recognized that freedom is primarily connected with man and the various ways of his existence. Unlike Sartre, Tischner was convinced that free choice does not consist of a sudden unbounded act of choice. According to the Kraków philosopher, what is most important in freedom is connected with the spiritual side of man. A free choice springs from it. The inner space of freedom is of agathological character and is inhabited by values created by man. The characteristic of the inner space of freedom was only partly drawn by Tischner. Therefore, in the second part of the article, the author attempts to reconstruct Tischner’s views on the structure of the ‘agathological space of freedom’.